2018
DOI: 10.1371/journal.pone.0189275
|View full text |Cite
|
Sign up to set email alerts
|

Missing depth cues in virtual reality limit performance and quality of three dimensional reaching movements

Abstract: BackgroundGoal-directed reaching for real-world objects by humans is enabled through visual depth cues. In virtual environments, the number and quality of available visual depth cues is limited, which may affect reaching performance and quality of reaching movements.MethodsWe assessed three-dimensional reaching movements in five experimental groups each with ten healthy volunteers. Three groups used a two-dimensional computer screen and two groups used a head-mounted display. The first screen group received th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 21 publications
0
31
2
1
Order By: Relevance
“…Furthermore, we developed and tested the method only for standard keyboard input and did not include support for the HTC Vive's motion controllers. Motions controllers are increasingly used to investigate naturalistic behavior, as they allow to track the hand movements of the participant [e.g., 52,53]. Future research needs to assess timing errors related to motion controllers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we developed and tested the method only for standard keyboard input and did not include support for the HTC Vive's motion controllers. Motions controllers are increasingly used to investigate naturalistic behavior, as they allow to track the hand movements of the participant [e.g., 52,53]. Future research needs to assess timing errors related to motion controllers.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have been investigating approaches to improve spatial perception in VR, such as depth cues [10], visual effects applied to 3D content [9], haptic feedback [11], freedom of movement [12], visual and audio cues [13], and virtual environment setup [6,14]. These approaches are interventions focusing on user interactions with VR applications.…”
Section: Spatial Perception In Virtual Environmentmentioning
confidence: 99%
“…The advent of modern stereoscopic virtual reality headmounted displays (HMDs, such as the Oculus Rift and HTC Vive) has allowed for improved depth perception in virtual environments [13]. The improvement of depth perception distortion is potentially to the point that the HMDs provide "immersion and depth perception on a level that proved sufficiently realistic for healthy young adults to perform natural reaching movements" [9]. Yet Lin et al suggest that stereoscopic depth cues could be part of the problem of depth perception distortion [16].…”
Section: Solutions To Depth Perception Distortionmentioning
confidence: 99%
“…Further research has found that the use of combined, or multimodal, sensory information (visual, aural, tactile) improves virtual environment presence and immersion [23], [12] and has a positive effect on depth perception [15], [9]. Hecht and Reiner suggest that audio and haptic stimuli are dominated by visual stimuli when only one or the other is coupled with the visual stimuli, but not both [11] and are more likely to go unnoticed.…”
Section: Solutions Using Multisensory Feedbackmentioning
confidence: 99%